Ties that bind : economic and political dilemmas of urban utility networks, 1800-1990 - Jacobson, Charles David (University of Pittsburgh Digital Collections, 2000)
"In this comparative historical study, Charles David Jacobson explores broad public policy concerns about private monopoly and the role of government in society, while at the same time addressing highly practical questions of how to make ownership, regulatory, and contracting arrangements for municipal services work better. For his analysis, Jacobson draws upon economic history to shed light on relationships between technology, market forces, and problems of governance that have arisen in connection with different utility networks. Focusing on four major U.S. cities - Boston, Seattle, San Francisco, and Pittsburgh - his study spans nearly two centuries, from the creation of centralized water systems in the first half of the nineteenth century and the building of electric utilities from the 1880s to the 1980s to an analysis of cable television franchising from the 1960s to the 1980s. Throughout, he argues, information and transactions costs played decisive roles in determining how well different ownership and regulatory arrangements functioned in different situations. Based upon extensive research in primary sources and using bold conceptualizations for his analysis, Jacobson's work moves us closer to understanding the political, economic, and technological dilemmas of modern urban utility networks."